2022
DOI: 10.1002/pld3.386
|View full text |Cite
|
Sign up to set email alerts
|

Multilocation proteins in organelle communication: Based on protein–protein interactions

Abstract: Protein-protein interaction (PPI) plays a crucial role in most biological processes, including signal transduction and cell apoptosis. Importantly, the knowledge of PPIs can be useful for identification of multimeric protein complexes and elucidation of uncharacterized protein functions. Arabidopsis thaliana, the best-characterized dicotyledonous plant, the steadily increasing amount of information on the levels of its proteome and signaling pathways is progressively enabling more researchers to construct mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…In agreement with the results of digital immunoblotting (Figure 2), new AtPM proteins only consisted of a small set (18.7%) of proteins exclusively localized to the PM when compared to the 330 multilocalizing proteins (MLPs) recorded according to experimental evidence codes (Supplemental Table S8). The recurrent identification of these proteins in the three AtPM fractions of this study indicated that these MLPs should not be discarded as contaminants, but rather argued for proteins shuttling or operating across organelles to regulate metabolic reactions or to transmit information from the surrounding environment (66). Within this line, the extracellular space and the Golgi apparatus were the two major co-localizing cellular components for the 112 MLPs, each accounting for 74 and 69 proteins, respectively.…”
Section: Identification Of New Pm-associated Proteins In Arabidopsismentioning
confidence: 84%
See 1 more Smart Citation
“…In agreement with the results of digital immunoblotting (Figure 2), new AtPM proteins only consisted of a small set (18.7%) of proteins exclusively localized to the PM when compared to the 330 multilocalizing proteins (MLPs) recorded according to experimental evidence codes (Supplemental Table S8). The recurrent identification of these proteins in the three AtPM fractions of this study indicated that these MLPs should not be discarded as contaminants, but rather argued for proteins shuttling or operating across organelles to regulate metabolic reactions or to transmit information from the surrounding environment (66). Within this line, the extracellular space and the Golgi apparatus were the two major co-localizing cellular components for the 112 MLPs, each accounting for 74 and 69 proteins, respectively.…”
Section: Identification Of New Pm-associated Proteins In Arabidopsismentioning
confidence: 84%
“…The further in silico analyses we performed on the 2165 PM protein set fitted typical traits of the plant PM, as inferred from functional grouping, membrane-anchoring mechanisms, hydrophobicity pattern, pI distribution, and PM-characteristic features of bitopic proteins ( Figures 3, 4 ). They also highlighted that the AtPM proteome mostly consisted of MLPs, as inferred from experimental evidence codes ( Tables S6, S7, S8 ), arguing for proteins shuttling or operating across organelles to regulate metabolic reactions or to transmit information from the surrounding environment (73). The plant PM is notably known to form ER–PM membrane contact sites (MCSs), defined as tight junctions tethered by specific proteins (74,75).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have also shown the remarkable significance of multilocation proteins in cell growth and development [41]. For instance, phosphorylation-related multilocation proteins can function as a "needle and thread" via protein-protein interactions (PPI), thus playing an important role in organelle communication and regulating plant growth [42]. Under these circumstances, there are mainly two ways for predicting multi-location proteins based on conventional classifiers: algorithm adaption and problem transformation.…”
Section: Sequences-based Ai Approachesmentioning
confidence: 99%
“…The genes of 2,429 ubiquitin-related proteins in the UniPro-tKB database were searched in the iSoybean mutant library, and 2,078 genes with 22,067 nonsynonymous or stop gain mutations were retrieved (Supplemental Table S1). Among them, 373 E3 ubiquitin ligases were used for protein-protein interaction network predictive analysis using the STRING 11.0 program (https://cn.string-db.org/) (Gong et al, 2021;Xiong et al, 2022Xiong et al, , 2021. The network showed that the E3 ubiquitin ligases GmARI1, GmARI2, GmARI3, and GmARI7 have multiple interacting proteins, which may be involved in multiple pathways.…”
Section: Improving Soybean Production Through New Design Associated W...mentioning
confidence: 99%